STUDY OF THE INFLUENCE OF THE DIAMETER OF MODIFIED TOOLS WITH INTERNAL COOLING CHANNELS UNDER DIFFERENT THERMAL FLOWS - França, P. H. P.; da Silva, L.R.R. (Revista de Engenharia Térmica, 2021)
In this work, the effect on heat generation at the chip-machine tool interface was studied by varying the diameter of internal grooves of a tool for the turning process. This tool is modified with internal channels that circulate water as a coolant through a closed system. As an output parameter, the maximum cutting temperature at the chip-tool interface was studied. The input parameters were the thermal flux present at the chip-tool interface and the diameter of the internal channels present in the cutting tool. All the analysis of variation of the internal channels of the tools and also of the thermal flow exerted on the chip-tool interface were carried out using the finite element method by the Ansys® Workbench 19.2 software. The main one was that the variation in the diameter of the tool's internal grooves does not expressly impact the machining specifications.